The cost and availability of therapeutic options in advanced prostatic carcinoma in Turkey - (:unkn) unknown (Kluwer Academic Publishers, 1992)
Advanced prostatic carcinoma may be treated by a variety of methods of endocrine manipulation which affect the production of androgens. This can either be done by bilateral orchiectomy or by a number of drugs. Orchiectomy has two advantages: low cost and being a once-only procedure. This report outlines the costs of various methods of hormonal treatment and compares them with each other in Turkey. © 1992 Akadémiai Kiadó.